EU law in populist times : crises and prospects / edited by Francesca Bignami, George Washington University. - Bignami, Francesca (Cambridge University Press, 2020)
The rise of Euroscepticism and populist backlash pose a dramatic challenge to the EU and highlight the EU's growing legal powers over core areas of state sovereignty. Authored by leading academics and policymakers, this book provides a comprehensive and cutting-edge analysis of the fields of EU law at the heart of contemporary political debates - economic policy, human migration, internal security, and constitutional fundamentals at the national level. Following the specialist contributions, the conclusion draws out critical, cross-cutting lessons for improving legitimacy and advancing the rule of law, rights and democracy in sovereignty-sensitive areas of EU law. Accessible to students, this volume is an invaluable resource for researchers and scholars of EU law and politics.